Karakter DAS Kambang Berdasarkan Analisis Morfometri dan Aspek Biofisik - Harisagustinawati Harisagustinawati; Aswandi Aswandi; Sunarti Sunarti (Universitas Batanghari Jambi, 2020)
Watershed (river basin) is a hydrological unit. DAS holds water, distributes water through a channel system from upstream to downstream, and ends in a body of water in the form of a lake or sea. Watershed is also an ecosystem, where the elements of organisms and the biophysical environment and chemical elements interact dynamically and in which there is a balance. DAS is seen as a unit of territorial unity where rainwater collects into a river to become a river flow. The factors that influence the characteristics of the watershed are morphometric factors and the biophysical aspects of the watershed. Watershed morphometry is a quantitative measure of the natural characteristics of the watershed, namely the geomorphological aspects of an area. This characteristic is related to the process of draining (drainage) of rainwater that falls in the watershed including the shape of the watershed, the area of the watershed, the density of the river (drainage), and the flow pattern. River flow is greatly influenced by the biophysical conditions of the Kambang watershed. Analysis of the biophysical conditions of the Kambang watershed includes analysis of soil types, land use, topographic conditions including slopes and contours, as well as the quality of Kambang river water. Considering the strategic designation of the Kambang watershed should be aligned with the watershed character.